2022
DOI: 10.1021/acsfoodscitech.1c00422
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Characteristic Markers in Honey of Various Botanical, Geographic, and Entomological Origins

Abstract: Honey has become a highly demanded product for consumers worldwide due to its unique taste and rich nutritional and medicinal values. However, it remains challenging to identify honey’s origin as well as determine its authenticity. This review aims at summarizing the progress of research carried out in the last decade toward discriminating honeys by using characteristic markers. Studies that illustrated melissopalynology, phytochemical substances, and biomacromolecular substances to identify honey origins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 117 publications
(171 reference statements)
1
17
0
Order By: Relevance
“…A similar observation was made by Wang et al [ 32 ], pointing out that tyrosine and formic acid could serve as markers of buckwheat pollen. A relatively high amount of tyrosine was found also in bee polyfloral honey from Baljuvon (TJK), the value corresponding to 3.31 ± 0.07 mg 100 g −1 FW.…”
Section: Resultssupporting
confidence: 83%
“…A similar observation was made by Wang et al [ 32 ], pointing out that tyrosine and formic acid could serve as markers of buckwheat pollen. A relatively high amount of tyrosine was found also in bee polyfloral honey from Baljuvon (TJK), the value corresponding to 3.31 ± 0.07 mg 100 g −1 FW.…”
Section: Resultssupporting
confidence: 83%
“…Searching for biomarkers of honey varieties is a task that has been carried out for over a dozen years [26]. For example, Cabras et al (1999) [27] showed that the marker for strawberry honey is 2,5-dihydroxyphenylacetic acid, called homogentisic acid.…”
Section: Discussionmentioning
confidence: 99%
“…is developed and optimized to obtain satisfactory performance. Bioactive chemical compounds typically found in honey samples can then be employed as targeted markers to assess honey authenticity [ 12 , 13 ], such as phenolic and polyphenolic compounds [ 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], sugars [ 4 , 21 ], volatile compounds [ 22 ], etc. However, the main drawback of targeted approaches is the requirement of chemical standards for quantitation purposes (and to guarantee compound identity), which is also a difficult and time-consuming task when dealing with complex sample matrices such as in the case of honey.…”
Section: Introductionmentioning
confidence: 99%